Police recruitment drive for 1,000 Inspectors - Daily Express, (KK) (Daily Express, 2012)
KUALA LUMPUR: Inspector General of Police Tan Sri Ismail Omar announced a Royal Malaysian Police recruitment drive for 1,000 Inspectors at upcoming convocations held at public and private Institutions of Higher Learning.